Connected minds/ technology and today's learners - Pedró Francesc (Paris: OECD, 2012)
"Digital media and connectedness are today an integral part of the lives of learners. This creates opportunities to fundamentally transform teaching and learning in formal education. This unique book tackles three questions to contribute to filling the knowledge gap. First, can the claim that today's students are New Millennium Learners, or digital natives, be sustained empirically?
Introduction : Why connectedness matters: It's not about technology, it's about connectedness ; Reasons for increased policy relevance ; How this report is organized -- How connectedness is shaping the economy and society: Overall economic impact on growth and productivity ; Implications for employment and skills ; The social uses of technology ; Beyond access: new digital divides -- How relevant connectedness is for young people: Most young people in OECD countries are fully connected ; The intensity and variety of uses of technology and connectedness ; Yet not all young people are equally connected -- Contrasting views about the digital generation: Alternative views evangelists, catastrophists and sceptics ; Is there room for yet another approach? -- What are the effects of attachment to digital media and connectivity?: A research challenge ; Cognitive skills development ; Limits of available evidence ; Social values and attitudes ; Overal conclusions -- Are learners' expectations changing?: A rationale for evolving expectations ; Teachers' estimates of students' expectations ; Are students more reluctant than expected to adopt technology in teaching? ; What works for students then? -- Emerging issues for education: Mapping out the issues ; Entertainment ; Information overload? ; Knowledge and learning ; Socialisation using digital tools ; Psychological issues: new problems or new opportunities? -- Key findings: Knowledge economy and society is supported by technology ; Young people already benefit from connectedness ; What matters is what young people do while they are connected ; Not enough research evidence yet to show critical effects on cognitive skills ; Expectations and behaviours of learners are not changing dramatically ; Stereotyped concepts can be misleading -- Implications for educational policy, research and practice: The agenda for the public debate ; Implications for policy makers ; implications for educational institutions and teachers ; Implications for parents ; Implications for research ; Concluding remarks.
"Centre for Educational Research and Innovation" --Cover.
Keywords: Educational Technology; Internet and youth; Educational- effect of technological